EFFECTS OF AROMATHERAPY MASSAGE ON THE SLEEP QUALITY AND PHYSIOLOGICAL PARAMETERS OF PATIENTS IN A SURGICAL INTENSIVE CARE UNIT - Özlü, Zeynep Karaman; Bilican, Pınar (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Surgical pain is experienced by inpatients with clinical, disease-related concerns, unknown encountersafter surgery, quality of sleep, restrictions in position after surgery is known to be serious. The study was conducted todetermine the effect of aromatherapy massage on quality of sleep and physiological parameters in surgical intensivecare patients.Materials and Methods: This is an experimental study. The sample of this study consisted of 60 patients who weredivided into two groups as experimental group and control group including 30 patients in each one. The participantswere postoperative patients, absent complications, who were unconscious and extubated. A data collection form onpersonal characteristics of the patients, a registration form on their physical parameters and the Richards-CampbellSleep Scale (RCSQ) were used to collect the data of the study.Results: The Richards-Campbell Sleep Scale indicated that while the experimental group had a mean score of 53.80 ±13.20, the control group had a mean score of 29.08 ± 9.71 and there was a statistically significant difference betweenmean scores of the groups. In a comparison of physiologic parameters, only diastolic blood pressure measuringbetween parameters in favor of an assembly as a statistically significant difference was detected.Conclusions: Results of the study showed that aromatherapy massage enhanced the sleep quality of patients in asurgical intensive care unit and resulted in some positive changes in their physiological parameters.